Pemanfaatan TikTok KPU Surakarta Sebagai Media Edukasi Pemilu Tahun 2024 - Melianto Suharno, Okta; Riyanto, Buddy; Kusumo Aji, Haryo (Solidaritas, 2025)
The modern era makes communication easier with the development of technology and information with the advent of the internet and the presence of social media. TikTok social media as one of the trending and much loved social media. TikTok makes it easy for its users to get educated through its content. KPU Surakarta is one of the creators of educational content for the 2024 election. This scientific study was made to determine the role of TikTok KPU Surakarta as an educational medium for the 2024 election.Keywords: Communication, Social Media, TikTok, Education, Elections